Allelic variation in GAD1 (GAD67) is associated with schizophrenia and influences cortical function and gene expression - Straub, R E; Lipska, B K; Egan, M F; Goldberg, T E; Callicott, J H; Mayhew, M B; Vakkalanka, R K; Kolachana, B S; Kleinman, J E; Weinberger, D R (Molecular psychiatry, 2007)
Cortical GABAergic dysfunction has been implicated as a key component of the pathophysiology of schizophrenia and decreased expression of the gamma-aminobutyric acid (GABA) synthetic enzyme glutamic acid decarboxylase 67 (GAD 67 ), encoded by GAD1 , is found in schizophrenic post-mortem brain. We report evidence of distorted transmission of single-nucleotide polymorphism (SNP) alleles in two independent schizophrenia family-based samples. In both samples, allelic association was dependent on the gender of the affected offspring, and in the Clinical Brain Disorders Branch/National Institute of Mental Health (CBDB/NIMH) sample it was also dependent on catechol- O -methyltransferase ( COMT ) Val158Met genotype. Quantitative transmission disequilibrium test analyses revealed that variation in GAD1 influenced multiple domains of cognition, including declarative memory, attention and working memory. A 5′ flanking SNP affecting cognition in the families was also associated in unrelated healthy individuals with inefficient BOLD functional magnetic resonance imaging activation of dorsal prefrontal cortex (PFC) during a working memory task, a physiologic phenotype associated with schizophrenia and altered cortical inhibition. In addition, a SNP in the 5′ untranslated (and predicted promoter) region that also influenced cognition was associated with decreased expression of GAD1 mRNA in the PFC of schizophrenic brain. Finally, we observed evidence of statistical epistasis between two SNPs in COMT and SNPs in GAD1 , suggesting a potential biological synergism leading to increased risk. These coincident results implicate GAD1 in the etiology of schizophrenia and suggest that the mechanism involves altered cortical GABA inhibitory activity, perhaps modulated by dopaminergic function.